Social Inquiry Learning Model in Improving Elementary School Students' Critical Thinking Skills - Bahtiar, Reza Syehma; Desiningrum, Noviana; Putri, Ellena Aurellia (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2024)
The importance of developing critical thinking skills in elementary education has gained increasing recognition, particularly through the implementation of inquiry-based learning (IBL) models. This study aims to evaluate the effectiveness of the social inquiry learning model in enhancing critical thinking skills among fourth-grade students at an public elementary school in Surabaya. Employing a qualitative case study methodology, data were collected through interviews, classroom observations, reflective journals, and document analysis. The thematic analysis revealed significant improvements in critical thinking for 75% of the participants, highlighting key themes such as "Engagement in Critical Thinking" and "Interaction Patterns in Learning Activities." These findings support the theoretical frameworks of Vygotsky and Piaget, demonstrating the model's applicability in non-Western educational contexts. The study suggests that culturally responsive teaching methods, incorporating social interactions and structured inquiry, can significantly enhance cognitive development. However, the limited scope of a single school and a small sample size suggest the need for further research across diverse settings. Future research should explore the long-term impacts of inquiry-based learning and the role of teacher preparation in implementing these strategies. This research underscores the importance of interactive, student-centered learning frameworks in fostering critical thinking and calls for a shift towards more dynamic educational approaches to prepare students for complex global challenges.